Effective Use of Field Trips in Educational Programming: A Three Stage Approach - Brian Myers; Linda Jones (EDIS)
The use of educational field trips has long been a major part of the education programming for both youth and adults. However, due to funding limitations, time constraints, and increased liability concerns many education professionals balk at requests for field trips. In spite of these concerns, well-planned field trips can be a valuable tool in the extension agents educational toolbox. This document is AEC373, one of a series of the Agricultural Education and Communication Department, UF/IFAS Extension. Original publication date May 2004. Reviewed February 2015.